Swept Source Optical Coherence Tomography Documenting Optic Nerve Involvement in an Aggressive T-Cell Lymphoma. (4th May 2021) - Areas, Layla Maris; Lavinsky, Fabio; Lavinsky, Daniel; Lindenmeyer, Rodrigo Leivas; Pakter, Helena Messinger; Catelli, Dayenne Helena; Finkelsztejn, Alessandro
ABSTRACT: Peripheral T-cell lymphomas (PTCLs) are a heterogeneous group of aggressive neoplasms. The involvement of ocular structures in haematological neoplasms is rare and usually associated with central nervous system involvement, which may occur as a result of orbital invasion and optic nerve infiltration. In this case report, we describe ocular findings using the novel swept source optical coherence tomography (SS-OCT) in a case of aggressive T-cell lymphoma. SS-OCT has faster scanning speed, deeper tissue penetration due to its longer wavelength laser of 1050 nm and wider scanning areas. In the present case, SS-OCT was helpful in documenting increased retinal nerve fibre layer thickness and prelaminar protrusion associated with visual loss in a patient with an aggressive T-cell lymphoma.